2023
DOI: 10.1007/s42452-023-05377-w
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer and flow around curved corner cylinder: effect of attack angle

Abstract: The aim of this study is to investigate the fluid flow structure and heat transfer from an isothermal cylinder with a curved corner radius ratio (r/R) of 0.5, and attack angle (α) is varied between 0° ≤ α ≤ 45°. The cylinder is subjected to airflow at a Reynolds number (Re) = 180 and Prandtl number (Pr) = 0.7. This study focuses on the effect of α on the fluid forces, Strouhal number, Nusselt number, and flow structure, and wake bubble size. The sensitivity of the time-mean drag and lift forces is investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A. et al [14] conducted an experimental study to investigate convection heat transfer enhancement from a circular cylinder in laminar pulsating flow with pulsating frequency from 1Hz to 12 Hz and Re from 1.02 10 4 to 2.04 10 4 . Abdelhamid et al, [15] introduced a numerical simulation for an isothermal curved cylinder with a corner radius ratio r/R (= 0.5), attack angle (α) varies between 0° ≤ α ≤ 45° at low Reynolds number Re (= 180). They observed that the fluid forces such as D and L are sensitive and have critical values at α ≈ 5° and α ≈ 12°, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…A. et al [14] conducted an experimental study to investigate convection heat transfer enhancement from a circular cylinder in laminar pulsating flow with pulsating frequency from 1Hz to 12 Hz and Re from 1.02 10 4 to 2.04 10 4 . Abdelhamid et al, [15] introduced a numerical simulation for an isothermal curved cylinder with a corner radius ratio r/R (= 0.5), attack angle (α) varies between 0° ≤ α ≤ 45° at low Reynolds number Re (= 180). They observed that the fluid forces such as D and L are sensitive and have critical values at α ≈ 5° and α ≈ 12°, respectively.…”
Section: Introductionmentioning
confidence: 99%